Sánchez Cordovés: the engineer who made possible women joining the radio - Espinosa-Mirabet, Sílvia (Historia y Comunicación Social, 2021)
This paper will reveal some unknown facets of the last director of Radio Barcelona before the Civil War. Joaquín Sánchez Cordovés, known for his excellent radio technical skills fascinated by the first sound cinema and pioneer of television in Spain, had a special care for popular music, which led him to organize a radio program to preserve it. Supporting this thesis, our research will reveal an unpublished audio piece: the only fragment of Sánchez Cordovés' voice recorded in the 1930s, at Radio Barcelona. The director of Radio Barcelona was also decisive for the incorporation of women into radio work.
Keywords: Sánchez Cordovés; Radio history; feminine speakers; Radio Barcelona; Audiovisual pioneer